Correlation of Carpal Tunnel Syndrome with Hand Grip Strength among Pregnant Females: A Cross-Sectional Study: Carpal Tunnel Syndrome and Grip Strength in Pregnancy - Sajjad, Ambreen Asghar; Naveed, Amna; Kaukab, Yusra; Wamiq, Alishba; Ashraf, Hanzallah Bin; Osama, Syed Muhammad (Pakistan Journal of Health Sciences, 2025)
Pregnancy induces physiological changes, including hormonal fluctuations and fluid retention, which may affect musculoskeletal function. These factors can reduce hand grip strength (HGS) and increase susceptibility to Carpal Tunnel Syndrome (CTS), caused by median nerve compression. CTS symptoms, including pain, numbness, and weakness, may hinder daily activities. Early detection during pregnancy is crucial for timely intervention. Objectives: To determine the frequency of hand-grip weakness (HGW) among pregnant women and to evaluate its correlation with clinical signs of CTS. Methods: This analytical cross-sectional study was conducted with 292 pregnant women aged 18–45 years, recruited through non-probability purposive sampling from multiple Karachi hospitals. HGS was measured with a Camry EH101 dynamometer following ASHT protocol; CTS was assessed using Phalen’s and Tinel’s tests. Data were analyzed using descriptive statistics, Chi-square, t-tests, ANOVA, and correlation analysis. Results: HGW was observed in 92.8% of participants. Phalen’s and Tinel’s tests were positive in 62.0% and 56.5%, respectively, and both showed significant associations with weak grip (p<0.001). Correlation analysis confirmed positive associations (Phalen’s r=0.301, Tinel’s r=0.264, p<0.001). Mean grip strength was lower in the weak group (16.11 ± 3.59) than in the normal group (23.93 ± 2.56; p<0.001), with no significant trimester differences. Conclusions: HGS measurement is a simple, non-invasive screening tool for early detection of CTS in pregnancy. Routine incorporation into antenatal care may facilitate timely management and preserve maternal hand function. Longitudinal studies are recommended.